2015
DOI: 10.1590/2176-9451.20.1.079-084.oar
|View full text |Cite
|
Sign up to set email alerts
|

Base of the skull morphology and Class III malocclusion in patients with unilateral cleft lip and palate

Abstract: OBJECTIVE: The aim of the present study was to determine the morphological differences in the base of the skull of individuals with cleft lip and palate and Class III malocclusion in comparison to control groups with Class I and Class III malocclusion. METHODS: A total of 89 individuals (males and females) aged between 5 and 27 years old (Class I, n = 32; Class III, n = 29; and Class III individuals with unilateral cleft lip and palate, n = 28) attending PUC-MG Dental Center and Cleft Lip/Palate Care Center of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 31 publications
3
22
0
9
Order By: Relevance
“…However, this differential pattern in cranial base was not observed in UCLP, unlike what we stated in our hypothesis and there were no statistically significant differences between neither CL1 nor CL3 control groups. Our findings are in accordance with previous study results, 21,23,33 and may be interpreted as scars due to surgical repairs are also important for the retrusive maxilla and Class III malocclusion tendency in UCLP patients and the influence of cranial base development remains unclear. This hypothesis might also be supported by Lin et al 21 who found no difference between non-syndromic CL3 patients and UCLP patients in cranial base measurements although maxilla was more retrusive in UCLP patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, this differential pattern in cranial base was not observed in UCLP, unlike what we stated in our hypothesis and there were no statistically significant differences between neither CL1 nor CL3 control groups. Our findings are in accordance with previous study results, 21,23,33 and may be interpreted as scars due to surgical repairs are also important for the retrusive maxilla and Class III malocclusion tendency in UCLP patients and the influence of cranial base development remains unclear. This hypothesis might also be supported by Lin et al 21 who found no difference between non-syndromic CL3 patients and UCLP patients in cranial base measurements although maxilla was more retrusive in UCLP patients.…”
Section: Discussionsupporting
confidence: 92%
“…There are only three studies comparing these two patient groups; two of them evaluate the skeletal features with some limitations, and one of them reports results based on only soft tissue parameters, while none of them analyzes sella turcica region in detail. 21,23,24 Therefore, the purpose of this study was to evaluate the size and morphology of the sella turcica together with the cranial base morphology in individuals with UCLP, and to compare it with individuals showing Class III discrepancy due to maxillary deficiency and individuals with normal Class I craniofacial development. The hypothesis was that the size and morphology of the cranial base and sella turcica of patients with UCLP and skeletal Class III were similar, but they showed differences from the skeletal Class I development pattern.…”
Section: Introductionmentioning
confidence: 99%
“…A morfologia do complexo craniofacial dos indivíduos portadores de fissuras labiopalatais tem sido muito discutida. A grande dúvida é se a fissura labiopalatal é um defeito congênito e restrito à maxila, ou se poderia fazer parte de um crescimento craniano anormal, com alterações estruturais em outras partes do crânio (Moss, 1956;Brader, 1957;Blaine, 1969;Dalh, 1970;Horswell;Gallup,1992;Trotman et al, 1993;Corbo et al, 2005;Cortés;Granic, 2006;Chang et al, 2005;Alkofide, 2008;Chang et al, 2014;Tinano et al, 2015).…”
Section: Discussionunclassified
“…O desenvolvimento do complexo craniofacial em pacientes com fissura labiopalatal tem sido estudado para estabelecer mecanismos e determinar fatores determinantes no desenvolvimento destes indivíduos. Um grande número de estudos mostra que a base do crânio é intrinsicamente diferente em forma e tamanho em pacientes com fissura labiopalatal (Moss, 1956;Cortés;Granic, 2006 (Brade, 1957;Tinano et al, 2015). A base do crânio de todos os indivíduos com fissuras labiopalatais difere-se dos indivíduos sem fissura.…”
Section: Classificação Das Fissuras Labiopalataisunclassified
See 1 more Smart Citation